2016
DOI: 10.1161/circulationaha.116.022188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of the Protein Farnesylation Inhibitors Lonafarnib, Pravastatin, and Zoledronic Acid in Children With Hutchinson-Gilford Progeria Syndrome

Abstract: Background Hutchinson-Gilford progeria syndrome is an extremely rare, fatal, segmental premature aging syndrome caused by a mutation in LMNA yielding the farnesylated aberrant protein, progerin. Without progerin-specific treatment, death occurs at an average age of 14.6 years from an accelerated atherosclerosis. A previous single-arm clinical trial demonstrated that the protein farnesyltransferase inhibitor, lonafarnib, ameliorates some aspects of cardiovascular and bone disease. This present trial sought to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 31 publications
3
135
0
5
Order By: Relevance
“…Farnesyl diphosphate synthase (FDPS) may promote the formation of misshapen nuclei upon progerin expression, and it is also a target of bisphosphonate drugs which are used for clinical trials against HGPS (Gordon et al, 2016; Varela et al, 2008). We found increased FDPS expression in progerin‐expressing cells, in human HGPS cells, and in mouse model (Figure 5a–c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farnesyl diphosphate synthase (FDPS) may promote the formation of misshapen nuclei upon progerin expression, and it is also a target of bisphosphonate drugs which are used for clinical trials against HGPS (Gordon et al, 2016; Varela et al, 2008). We found increased FDPS expression in progerin‐expressing cells, in human HGPS cells, and in mouse model (Figure 5a–c).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been suggested that FDPS could promote the formation of misshapen nuclei upon progerin expression, and it is also a target of bisphosphonate drugs which are used for clinical trials against HGPS (Gordon et al, 2016; Varela et al, 2008). Bisphosphonates target FDPS, and according to our results, FDPS levels increased upon progerin and prelamin A expression (i.e., in HGPS‐derived cells and Zmpste24 ‐deficient bone, respectively) and targeting FDPS with pamidronate overcame progerin‐induced senescence and misshapen nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Investigations into the mechanism and treatment of HGPS may yield new insights into the treatment of age-related cardiovascular disease. 16 …”
mentioning
confidence: 99%
“…3 Characterized by accelerated aging, HGPS has a prevalence of ≈1 in 20 million living individuals or ≈350 children worldwide at any given time. Without treatment, children with HGPS, who have completely normal intellectual development, die of atherosclerotic cardiovascular disease at the average age of 14.6 years.…”
mentioning
confidence: 99%